Foodsheds in Virtual Water Flow Networks: A Spectral Graph Theory Approach - Kshetry, Nina; Varshney, Lav R. (Frontiers in ICT, 2017)
A foodshed is a geographic area from which a population derives its food supply, but a method to determine boundaries of foodsheds has not been formalized. Drawing on the food-water energy nexus, we propose a formal network science definition of foodsheds by using data from virtual water flows, i.e. water that is virtually embedded in food. In particular we use spectral graph partitioning for directed graphs. If foodsheds turn out to be geographically compact, it suggests the food system is local and therefore reduces energy and externality costs of food transport. Using our proposed method we compute foodshed boundaries at the global-scale, and at the national-scale in the case of two of the largest agricultural countries: India and the United States. Based on our determination of foodshed boundaries, we are able to better understand commodity flows and whether foodsheds are contiguous and compact, and other factors that impact environmental sustainability. The formal method we propose may be used more broadly to study commodity flows and their impact on environmental sustainability.